Implementation of Progressive Web App on Dropship Data Management Application to Anticipate Product Order Errors - Ramdani, Hasbi Taobah; Ainun, Nur; Muktamar B, Ahmad (Yayasan Gema Bina Nusantara, 2023)
Digital business trends during the COVID-19 pandemic have increased. One of the digital businesses that can be run during a pandemic, one of which is the dropship business, has a fairly low risk because it does not require large capital and infrastructure preparation. Dropship data management without a data management system can make it difficult for drop shippers to manage and view customer, product, and supplier data. Besides that, without a data management system, it is very likely that the drop shipper will make an error in ordering and shipping the product. This research will discuss the creation of a data management application for drop shipping to cover dropship data management problems. The developed application will be web-based using a Progressive Web App (PWA) so that it can have better performance with a cache and a display that resembles a mobile application.